Toward temporal evolution of consolidation in fluid-saturated poroelastic media with various permeable conditions. (April 2023) - Wang, Luyu; Yin, Zhen-Yu; Han, Gang; Yu, Meilu
Abstract: Previous studies have revealed that consolidation is a time-dependent process and highly depends on the permeable properties of boundary as well as the loading modes. This work investigates the characteristics of temporal evolution during consolidation in fluid-saturated poroelastic media. After a revisit on Biot's theory, a poroelastic model is established as a prototype that is widely existing in practice. Then, a solution strategy is proposed based on differential operator method and series expansions. The basic solutions are derived and consist of the kernel functions. The solutions in general situations are extended by these basic solutions. Especially, as one of the novelties, the impermeable and permeable boundaries with different loading modes are integrated into this framework. Several different loading distributions are considered, including time-constant periodic loading and uniform loading on the infinite and finite boundaries. Later, the solutions are verified by comparing with the results calculated by numerical method. Based on this, a series of numerical tests is performed to study consolidation behaviours of a poroelastic medium. Some insights to the characteristics of temporal evolution during consolidation are explored, where the influences of drainage effect, loading modes and material properties on this process are analysed.